About Problem Approach in Teaching Non-Native Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Language teaching is impossible without the development of students' cognitive activity, it is necessary to develop a problem approach to the content of textual and lexico-grammatical material, to its selection and organization. It is recommended to lead problem-searching tasks in stages, gradually increasing their complexity, remembering that the degree of complexity of the tasks depends on the level of language proficiency of students, mastery of textual material; the tasks should be accessible; carry new, interesting information; provide access to communication. Problem-based learning is effectively realized in joint collective activity, which is the basis of communication learning.